PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA ASSEMBLR EDU TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Salsa Maria; Laily Alindra, Afridha; Mustikaati, Wina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science literacy skills are one of the most important learning in the science learning process so that students are able to apply science appropriately. This helps students not only see, but also apply scientific ideas relevantly in their daily activities. However, the science literacy skills of elementary school students in Indonesia are still relatively low. The application of the project based learning model is one of the learning that can improve the science literacy skills of elementary school students. The purpose of this study was to determine the effect of the Project Based Learning learning model assisted by Assemblr Edu on the science literacy skills of elementary school students. The method used was a quasi-experimental with a non-equivalent control group design in science learning on energy transformation material. The instrument used was a science literacy test. The results of the regression calculation study showed an effect of the project based learning model of 36.1% and the N-Gain score of the experimental class was 0.58 while the control class was 0.49. The conclusion obtained from this study is that there is an effect of the project based learning model assisted by the assembly edu media on the science literacy skills of elementary school students.